Strategi Optimalisasi Pemberdayaan UMKM di Kabupaten Ponorogo - Sri Andayani; Nekky Rahmiyati (Journal of Business and Economics Research (JBE), 2020)
The number of MSMEs in Ponorogo Regency based on data from the Office of Cooperatives and MSMEs in JATIM Province was 207,561. The number will continue to increase in the following years, with an increase in quantity, it does not mean that Micro and Small Enterprises (MSEs) have no problems, Problems always exist including: Low productivity, caused by low quality of human resources, especially in management, organization, technology mastery, and marketing. Limited access to capital. The situation is very difficult for MSMEs to increase business capacity or develop competitive products, although the government has provided solutions through various cheap and easy credit scheme schemes, but there are still many MSMEs that are difficult to reach. With that, we conducted a research entitled "Optimization Strategy for Empowerment of SMEs in Ponorogo Regency. The problem in this study is: What is the strategy to optimize the empowerment of MSMEs in Ponorogo Regency? While the purpose of this study is to find out: 1. Empowerment of MSMEs that have been carried out by the Government, through the relevant Dinas in Kabupaten Ponorogo. 2. How to Optimize the Strategy for Empowerment of MSMEs (which should be) carried out in Ponorogo Regency. Research Methods: Research Sites in Ponorogo Regency, a. Primary data collection of respondents questionnaire instrument as many as 100 MSME actors b. Data analysis using SWOT analysis, c. then an Optimization Strategy for empowering MSMEs was made. Research Results: Based on SWOT Analysis, the results are obtained: In the current internal condition of MSMEs in Ponorogo Regency the position of strength is 1.67 while the weakness is 1.46 which is higher than the weakness. While the opportunity factor (O) has a score of 1.57 and the threat factor (T) with a score of 1.25, so there is still a higher chance of the threat. So that the IFAS score is 3.13 and the EFAS score is 2.82. Based on these conditions, then: a) In quadrant I (S o Strategy) Aggressive strategy: a general strategy that can be carried out by MSEs is to use the power of MSMEs to take every advantage on the opportunities that exist. b) In quadrant II (WO Strategy) Turn Arraund Strategy, SMEs can make excellence on opportunities as a reference to focus activities by avoiding weaknesses. c) In quadrant III (WT Strategy) Deversification Strategy Minimize all weaknesses to deal with each threat. d) In quadrant IV (S-T Strategy) Make every strength to deal with each threat by creating diversification to create opportunities